Assessment of Seine Net Selectivity in Lake Maninjau, Agam Regency, West Sumatra - Indonesia - Amelia, Dea; Ramdhani, Farhan; Lisna, Lisna; Ramadan, Fauzan; Nurhayati, Nurhayati; Heltria, Septy (Sriwijaya Journal of Environment, 2024)
Using small mesh sizes on sein net in Lake Maninjau may lead to overexploitation. Research assessing selectivity of this fishing gear in this area is not conducted yet. Thus, this research aims to determine selectivity of seine net fishing gear operated in Lake Maninjau, Tanjung Raya District, Agam Regency, West Sumatra Province. There were seven units of seine net with 5 mesh sizes connected mesh sizes measuring 1.5 inches, 2 inches, 2.5 inches, 3 inches, to 3.5 inches that were assessed in this study. The results revealed that more than five species of fish were caught with various sizes, namely Tilapia (Orheochromis niloticus), Betutu (Oxyeleotris marmorata), Louhan (Amphilophus trimaculatus), Patin (Pangasius sp), and Sapu-sapu (Hypostomus plecostomus). Considering minimum landing size, 1,021 (82%) catch of Tilapia are suitable for catching meanwhile 231 (18%) are under minimum size for catch.